Reseña de Casas Gómez, M. e I. Penadés Martínez (Coords.), M. T. Díaz Hormigo (ed.) (1998), Estudios sobre el Diccionario de uso del español de María Moliner, Cádiz, Universidad de Cádiz. - Rojas Pichardo, Juan Pedro (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–> Se trata de reseña de Casas Gómez, M. e I. Penadés Martínez (Coords.), M. T. Díaz Hormigo (ed.) (1998), Estudios sobre el Diccionario de uso del español de María Moliner, Cádiz, Universidad de Cádiz.